2021
DOI: 10.7717/peerj.11383
|View full text |Cite
|
Sign up to set email alerts
|

Denouncing the use of field-specific effect size distributions to inform magnitude

Abstract: An effect size (ES) provides valuable information regarding the magnitude of effects, with the interpretation of magnitude being the most important. Interpreting ES magnitude requires combining information from the numerical ES value and the context of the research. However, many researchers adopt popular benchmarks such as those proposed by Cohen. More recently, researchers have proposed interpreting ES magnitude relative to the distribution of observed ESs in a specific field, creating unique benchmarks for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Effect size distributions can be useful to calibrate your understanding of effect sizes in different areas but they are not without fault. Panzarella et al (2021) demonstrated that in the studies that cited effect size distributions, most used them to directly interpret the effect sizes they observed in their study (e.g., "in this study we found a 'large' effect, which means. .…”
Section: Effect Sizementioning
confidence: 87%
See 2 more Smart Citations
“…Effect size distributions can be useful to calibrate your understanding of effect sizes in different areas but they are not without fault. Panzarella et al (2021) demonstrated that in the studies that cited effect size distributions, most used them to directly interpret the effect sizes they observed in their study (e.g., "in this study we found a 'large' effect, which means. .…”
Section: Effect Sizementioning
confidence: 87%
“…The most difficult part of an a priori power analysis is justifying your smallest effect size of interest. Choosing an effect size to use in power analysis and interpreting effect sizes in your study requires subject matter expertise (Panzarella et al, 2021). You must decide what effect sizes you consider important or meaningful based on your understanding of the measures and designs in your area.…”
Section: Effect Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Researchers typically make no interpretations regarding magnitude or rely on procedures with questionable validity (Farmus et al, in press). These questionable approaches may include using benchmark standards for interpreting effect size magnitude (e.g., small, medium, and large interpretations, see Cohen, 1988) or interpreting magnitude by comparing the effect size in a given study to the distribution of effect sizes in a discipline or research area (Panzarella et al, 2021). These practices become troublesome when discussing the study's practical significance, as one's understanding of the impact of the effects is affected by missing, questionable, or flawed interpretations of magnitude (Panzarella et al, 2021).…”
Section: Haphazard Interpretation Of the Magnitude Of Effect Size (Hime)mentioning
confidence: 99%
“…These questionable approaches may include using benchmark standards for interpreting effect size magnitude (e.g., small, medium, and large interpretations, see Cohen, 1988) or interpreting magnitude by comparing the effect size in a given study to the distribution of effect sizes in a discipline or research area (Panzarella et al, 2021). These practices become troublesome when discussing the study's practical significance, as one's understanding of the impact of the effects is affected by missing, questionable, or flawed interpretations of magnitude (Panzarella et al, 2021). More precisely, Haphazardly Interpreting the Magnitude of Effect Sizes (HIMEing) can impact the interpretation of a particular finding by distorting the true practical significance of the effect.…”
Section: Haphazard Interpretation Of the Magnitude Of Effect Size (Hime)mentioning
confidence: 99%